Effects of Propolis Extract Supplementation during Pregnancy on Stress Oxidative and Pregnancy Outcome: Levels of Malondialdehyde, 8-Oxo-2′-Deoxogunosine, Maternal Body Weight, and Number of Fetuses - Wibowo, Joko Wahyu; Fasitasari, Minidian; Zulaikhah, Siti Thomas (Jurnal Kedokteran Brawijaya, 2021)
Oxidative stress is related to pregnancy complications that could increase maternal and infant mortality. This study aimed to determine the effect of propolis extract supplementation during pregnancy on oxidative stress level and pregnancy outcomes utilizing Malonedealdehyde (MDA) and 8-Oxo-2′-Deoxogunosine (8-OHdG) levels, maternal body weight, and the average number of fetuses as the parameters. The study was conducted by using a posttest only control group design on 24 pregnant Wistar rats, which were divided into four groups. Group I was control, Group II-IV were the treatment groups given propolis extract of 1.8mg, 3.6mg, and 7.2mg/200gBW/day, respectively. The standard feed given was AIN93G dose of 20g/day and distilled water ad libitum. Propolis extract was given using a gastric feeding tube every morning for 20 days. At the end of the treatment, body weight was meisured and blood collected for assessed MDA and 8-OHdG levels  by ELISA method  and then we performed abdominal surgery to count number of fetuses. The result are there were decreasing level of MDA and 8-OHDG by administration of propolis significantly (p<0.05) group: I: 2,04±0,091, II: 1,55±0,067, III: 1,05±0,176, IV: 0,73±0,075 (mmol/mL) (p=0.001); 8 OHdG level (ng/mL) group I: 10,02±0,403, II: 8,60±0,078, III: 7,89±0,051, IV: 7,53±0,063 (p=0,001). Average of maternal body weight (g) were increased: group I: 228,33±3,93, II: 237,17±4,36, III: 244,83±4,02, IV: 248,00±5,76 (p=0,001) and Average number of fetuses tend to increased as well, group I : 8,5±0,05, II: 7,8±0,41, III: 9,5±1,05, IV: 9,6±0,52 (p=0,02). The conclusion of this research are supplementation of propolis extract in pregnant rats can reduce oxidative stress and improve pregnancy outcomes.